KONSELING LINTAS BUDAYA DAN AGAMA DENGAN PENDEKATAN REBT SEBAGAI TINDAKAN PREVENTIF FENOMENA RADIKALISME AGAMA - Kartini, Kartini (Hudan Lin Naas: Jurnal Ilmu Sosial dan Humaniora, 2022)
The phenomenon of religious radicalism is a phenomenon that worries many people. An organization that disturbs many organizations continues to grow rapidly in every country, especially Indonesia. What is a deep concern is when radicalism is rife in religion, so it requires an approach to reduce the phenomenon of radicalism. This study uses a library research method or a qualitative research type of literature research with the result that preventive measures can use the REBT approach which leads to the hope that the thoughts of religious radicalism can be controlled properly.